2010
DOI: 10.4269/ajtmh.2010.10-0036
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Envenomation Among Children: Clinical Manifestations and Outcome (Analysis of 685 Cases)

Abstract: Our objective was to characterize both epidemiologically and clinically manifestations after severe scorpion envenomation and to define simple factors indicative of poor prognosis in children. We performed a retrospective study over 13 years (1990–2002) in the medical intensive care unit (ICU) of a university hospital (Sfax-Tunisia). The diagnosis of scorpion envenomation was based on a history of scorpion sting. The medical records of 685 children aged less than 16 years who were admitted for a scorpion sting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
2
18

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 50 publications
7
117
2
18
Order By: Relevance
“…First, in this study the symptoms in none of the patients were accompanied by neurological complications, from which no patients were suffering during the hospitalization. This is in contrast to previous studies conducted in Iran and other countries, which repeatedly reported neurological symptoms in scorpion-sting patients during hospitalization and considered such symptoms to be the major signs (6,(12)(13)(14). All patients in this study were past age 11, while in Pipelzadeh and colleagues study, the majority of cases were children aged less than 12 years.…”
Section: Discussioncontrasting
confidence: 52%
“…First, in this study the symptoms in none of the patients were accompanied by neurological complications, from which no patients were suffering during the hospitalization. This is in contrast to previous studies conducted in Iran and other countries, which repeatedly reported neurological symptoms in scorpion-sting patients during hospitalization and considered such symptoms to be the major signs (6,(12)(13)(14). All patients in this study were past age 11, while in Pipelzadeh and colleagues study, the majority of cases were children aged less than 12 years.…”
Section: Discussioncontrasting
confidence: 52%
“…The severity of the envenomation is related to the age of the victim, the size of the scorpion, the season of the sting and time which had elapsed between the sting and the hospitalization [8,9]. A severe scorpion sting envenomation occurs in children with a 3.9-10% fatality, which is irrespective of the intensive care management, in Israel, Turkey and India [10][11][12][13]. No clinically useful demographic or epidemiological data to guide the decision making regarding the need for the intensive care unit admission for the paediatric victims of scorpion sting, was noted by Bosnak et al, in Turkey [12].…”
Section: Introductionmentioning
confidence: 99%
“…Hastaları sınıflandırmak adına kimi çalışma-cılar "pediatric mortalite risk skoru (PRISM)" kullanırken bir kısmı da evreleme yöntemi (evre 1; lokal bulgular, evre 2; sistemik bulgular, evre 3; kardiyojenik şok ve/veya pulmoner ödem veya koma yada konvülziyon gibi ağır nöro-lojik bulgular) kullanmıştır (7,8). Laboratuvar imkanları-nın artması ile troponin, BNP, ardından N-terminal-pro BNP kullanılarak sistemik bulgular anlaşılmaya çalışılmış, EKO imkanlarının artması ile kalp yetmezlikleri, hipoaktif alanlar erken fark edilmeye başlanmıştır (35)(36)(37)(38)(39) Genel kanı sadece lokal bulguları olan hastaların yoğun bakım ihtiyacı olmadığı yönündedir.…”
Section: Bulgularunclassified
“…Laboratuvar imkanları-nın artması ile troponin, BNP, ardından N-terminal-pro BNP kullanılarak sistemik bulgular anlaşılmaya çalışılmış, EKO imkanlarının artması ile kalp yetmezlikleri, hipoaktif alanlar erken fark edilmeye başlanmıştır (35)(36)(37)(38)(39) Genel kanı sadece lokal bulguları olan hastaların yoğun bakım ihtiyacı olmadığı yönündedir. Ancak çocuklarda hastaların basamakları tahmin edilemeyen sürelerde atlayabildikleri görülmüştür (7). Bu yüzden biz tüm çocuk hastaların hiçbir şikayeti olmasa bile en az 24 saat yakın-dan izlenmesinin uygun olacağı kanaatindeyiz.…”
Section: Bulgularunclassified
See 1 more Smart Citation